Spatial Inequalities and Recovery Patterns in Central European Tourism After the Pandemic - Turnai, Zsófia; Horváthné Kovács, Bernadett; Gábor, Koncz; Barna, Róbert (Acta Carolus Robertus, 2025)
In the decade preceding the COVID-19 pandemic, global international tourism showed continuous growth, but the 2020 crisis highlighted the sector’s extraordinary sensitivity and vulnerability, fundamentally shaking the industry. Our study examines the patterns of tourism recovery in regions of four Central European countries: Austria, the Czech Republic, Hungary, and Slovakia. The research is based on regional-level data from the period between 2018 and 2022, with a particular focus on the development of overnight stays and tourism capacities. According to our hypothesis, tourist destinations and regions with more pronounced seasonal fluctuations are more sensitive to crises due to their characteristics, yet – thanks to their favourable localization conditions – they may also be capable of quicker recovery. We used quantile maps to represent spatial inequalities for the following variables: domestic and foreign overnight stays in tourist accommodations, changes compared to the two previous years and 2019, number of overnight stays, number of beds, and number of accommodations. We used clustering models (hierarchical, K-means) to determine the spatial pattern of the observations. According to the analysis results, the regions’ tourism performance showed significant spatial differences in the post-COVID-19 period. Some of the analysed regions had a more dynamic recovery capacity: in more than half of the regions, the number of overnight stays in 2022 exceeded the 2020 figure, while in 40% of them, it did not even reach the pre-COVID level of 2019. It was found that the recovery was faster in the regions that had experienced a significant decline due to COVID-19. A common characteristic of the regions is that areas dependent on foreign visitor traffic experienced the greatest decline, while regions relying on domestic tourism showed a quicker recovery.